Hematopoietic stem cell transplantation for pediatric acute lymphoblastic leukemia - Daudt, Liane Esteves; Correa, Ana Carolina Ribeiro; Zanette, Antonella; Macedo, Antonio Vaz de; Breviglieri, Carla Nolasco Monteiro; Kuwahara, Cilmara; Castro Junior, Cláudio Galvão de; Domingues, Luciana dos Santos; Klinger, Paulo; Ikoma, Maura; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
This article details the 2025 consensus update from the Brazilian Group for Pediatric Bone Marrow Transplantation and the Brazilian Society for Pediatric Oncology regarding hematopoietic stem cell transplantation (HSCT) for pediatric acute lymphoblastic leukemia (ALL). Allogeneic HSCT is the standard treatment for high-risk or relapsed ALL. Key indications include, in first remission, very high risk patients defined by primary induction failure or positive minimal residual disease (MRD) after consolidation. In second remission, it is indicated for early bone marrow relapse, early isolated extramedullary B-cell relapse, and all T-cell ALL relapses. The consensus recommends myeloablative conditioning as standard, preferring total body irradiation based regimens for children over 2–3 years old. The preferred donor hierarchy is a matched sibling, followed by a matched unrelated donor, with bone marrow being the preferred cell source. Post-HSCT monitoring of MRD is critical for guiding interventions and identifying relapse. This document serves as an essential, updated guide for clinical decision-making in this field.